Miliusa microphylla (Annonaceae), a new species from Thailand as evidenced by morphology and plastid phylogeny, with M. glandulifera, a new record for Thailand - Damthongdee, Anissara; Sinbumroong, Aroon; Rueangruea, Sukid; Kaitongsuk, Saksan; Ue-Aree, Phasit; Jongsook, Hathaichanok; Chaowasku, Tanawat (Phytotaxa, 2022)
On the basis of expansive molecular phylogenetic analyses of the genus Miliusa (Annonaceae) utilising up to seven plastid DNA regions, four major clades are identified: clades A, B, C and D. Members of clade C possess axillary inflorescences and crescent-shaped to semicircular glandular structures at the base or (slightly) higher inside the inner petals. In this clade, accessions of M. mollis are recovered as a monophyletic group, divided into two major clades. One of them is recognised as a new species, M. microphylla, which differs from the other (M. mollis) in the following characters: pedicel length, as well as glandular structures and indumentum on the inner petals. The new species is endemic to southeastern Thailand, whereas M. mollis has a much wider distribution (central, eastern, northeastern, northern and peninsular Thailand plus Cambodia and Vietnam). In addition, M. glandulifera, a new record for Thailand, is retrieved as the sister group of a clade composed of M. microphylla and M. mollis. The name M. glandulifera is lectotypified and the description of M. glandulifera is emended, with the information on mature monocarps added. The conservation status of M. microphylla and M. glandulifera is provisionally assessed. A revised key to the species in clade C in Thailand is provided. The phylogenetic position of M. nakhonsiana and M. sessilis in clade C, as well as of M. chantaburiana and M. eupoda in clade B is confirmed for the first time.